Enzymatic bioreactor for simultaneous electrosynthesis and energy production. (1st May 2016) - Mazurenko, Ievgen; Etienne, Mathieu; Kohring, Gert-Wieland; Lapicque, François; Walcarius, Alain
Abstract: The proof-of-concept for enzymatic electrosynthesis with simultaneous energy production has been demonstrated by using the regioselective conversion of D-sorbitol to D-fructose by D-sorbitol dehydrogenase as a model reaction. The bioreactor was composed of two electrodes, a carbon felt bioanode modified by multi-walled carbon nanotubes (MWCNT) containing D-sorbitol dehydrogenase immobilized in a silica matrix and an oxygen gas-flow cathode. The electrochemical regeneration of the NAD + cofactor at the bioanode was achieved by using a poly(methylene green) mediator electrodeposited on the carbon felt/MWCNT electrode. The conversion rate was 1.18 mg day −1  cm −3 and an energy power output up to 14.6 μW cm −3  at 0.1 V was reached.